Heparin is more effective than apixaban in inhibiting in vitro contact activated coagulation. (25th November 2020) - Engelen, M.M; Van Laer, C; Jacquemin, M; Vandenbriele, C; Peerlinck, K; Verhamme, P; Vanassche, T
Abstract: Introduction: Contact of blood with artificial surfaces such as mechanical support devices, catheters, and mechanical heart valves activates the contact activation (CA) pathway of coagulation. Furthermore, recent animal data and clinical studies suggest a more important contribution of CA in pathological thrombus formation in other cardiovascular diseases. Direct oral anticoagulants (DOACs) are recommended as first-line treatment in most patients who require long-term anticoagulation. However, because DOACs directly inhibit a single downstream coagulation factor (thrombin (fXIIa) or factor Xa (fXa)), it has been suggested that their efficacy could be reduced in the presence of strong activation of the CA pathway as compared to anticoagulants that target multiple, more upstream located coagulation factors. Purpose: To compare the efficacy of a DOAC (apixaban) and heparin to suppress thrombin generation in the presence of strong CA pathway activation. Methods: Pooled platelet-poor plasma was spiked with either apixaban (dissolved in DMSO and PBS) or unfractionated heparin to achieve therapeutic plasma levels. SynthASil, a commercially available mixture of phospholipids and silica, was used to stimulate the CA pathway in two different dilutions (1–80 and 5–80). Downstream coagulation was accessed by Thrombin Generation Test using Thrombinoscope by Stago and associated Thrombin Calibrator (activity 640 nM). The endogenous thrombin potential (area under the thrombin generation curve; ETP), peak thrombin generation (PTG), time to peak (ttPeak) and time to start (ttStart) were accessed. Results: With decreasing concentrations of apixaban, stimulation with the lower dose SynthASil reveals an increasing ETP and PTG. As expected, ttPeak and ttStart decreased. Even supratherapeutic levels of apixaban (i.e. 1120 ng/mL) could not inhibit thrombin from being generated, in striking contrast with UFH where no thrombin was formed. Using a five times higher dose of SynthASil showed comparable ETP for all concentrations of apixaban, allocated around the control value. PTG, however, slightly increased with decreasing concentrations of apixaban. ttPeak and ttStart slightly decreased. Except for the subtherapeutic UFH concentration of 0, 114 IU/mL, no thrombin was generated with UFH. Conclusion: UFH is more effective in inhibiting downstream thrombin generation compared to apixaban as a response to activation of the CA pathway in vitro. These findings could help explain why direct inhibitors were not able to show non-inferiority in patients with mechanical heart valves and support the development of specific CA pathway inhibitors for patients with conditions that activate the CA pathway. Funding Acknowledgement: Type of funding source: None